Green investing and political behavior - Florian Heeb; Julian Kölbel; Stefano Ramelli; Anna Vasileva (Leibniz Institute for Financial Research SAFE, 2024)
A fundamental concern about green investing is that it may crowd out political support for public policy addressing negative externalities. We examine this concern in a preregistered experiment shortly before a real referendum on a climate law with a representative sample of the Swiss population (N = 2,051). We find that the opportunity to invest in a climate-friendly fund does not reduce individuals' support for climate regulation, measured as political donations and voting intentions. The results hold for participants who actively choose green investing. We conclude that the effect of green investing on political behavior is limited.
Keywords: D14; H42; G18; P16; 330; Behavioral Finance; Climate Change; ESG; Externalities; Sustainable Finance; Political Economy; Voting Behavior